2022
DOI: 10.1101/2022.10.31.22281764
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 antibody prevalence among industrial livestock operation workers and nearby community residents, North Carolina, USA, 2021-2022

Abstract: Industrial livestock operations (ILOs), particularly processing facilities, emerged as centers of coronavirus disease 2019 (COVID-19) outbreaks in spring 2020. Confirmed cases of COVID-19 underestimate true prevalence. To investigate prevalence of antibodies against SARS-CoV-2, we enrolled 279 participants in North Carolina from February 2021 to July 2022: 90 from households with at least one ILO worker (ILO), 97 from high-ILO intensity areas (ILO neighbors – ILON), and 92 from metropolitan areas (Metro). Part… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…[ 24 ] observational USA mask mandates for reducing transmission nucleic acid or antigen mandate data Gigot et al . [ 25 ] observational USA masks for reducing transmission saliva antibody testing questionnaire Goncalves et al . [ 26 ] observational Brazil masks for reducing transmission RT-PCR or antibody testing (non-specific) interview Hast et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 24 ] observational USA mask mandates for reducing transmission nucleic acid or antigen mandate data Gigot et al . [ 25 ] observational USA masks for reducing transmission saliva antibody testing questionnaire Goncalves et al . [ 26 ] observational Brazil masks for reducing transmission RT-PCR or antibody testing (non-specific) interview Hast et al .…”
Section: Resultsmentioning
confidence: 99%
“…Forty-seven studies reported on the effectiveness of masks for reducing transmission of SARS-CoV-2 as their primary outcome: 24 studies (two RCTs, 22 observational) in community settings [ 14 18 , 20 , 21 , 23 , 25 27 , 29 , 33 , 34 , 36 41 , 43 , 44 , 46 , 48 ] and 23 observational studies in healthcare settings [ 50 , 53 61 , 63 66 , 68 , 69 , 75 77 , 81 , 82 , 84 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations